SAT0571 Role of Obesity in the Expression of Cytokines and Metalloproteinases in Human Osteoarthritis Chondrocytes. (10th June 2014) - Perniola, S.; Lacarpia, N.; Bizzoca, R.; Natuzzi, D.; Notarnicola, A.; Moretti, B.; Lapadula, G.; Iannone, F.
Abstract : Background: During osteoarthritis (OA), articular cartilage degradation is essentially due to the increase of the expression of pro-catabolic factors, such as nerve growth factor (NGF), interleukin-17 (IL-17) that activate the local synthesis of metalloproteases (mainly MMP-13) and aggrecanase (mainly ADAMTS-5) leading to the breakdown of type II collagen and proteoglycans with microscopic and macroscopic damage. In obesity, adipose visceral tissue over-produces pro-flogistic and pro-catabolic mediators such as tumour necrosis factor (TNF-α), IL-1β, IL-17, NGF. In addition, the adipocytes produce specific adipokines and leptin has been involved in the pathophysiology of OA. Leptin has been reported to selectively promote the synthesis of pro-flogistic mediators and proteases in OA chondrocytes and thus representing a possible pathogenic link between obesity and OA. Objectives: To evaluate 1) the histological differences of the articular cartilage between obese and normal- weight patients with OA, 2) the differences in expression of MMP-13, ADAMTS-5, NGF, IL-17, IL-10 and leptin in the articular cartilage of obese and normal-weight OA patients, 3) the correlation between the expression of these molecules and body mass index (BMI) and cartilage damage. Methods: Articular cartilage of the tibial plateau of 19 obese patients (13 women, 6 men; BMI between 31-37; age 41-84 years) and 10 normal-weight patients (6 women, 4 men; BMI between 21-23; age 28-73 years) undergoing surgery knee replacement for OA. Classical histology (toluidine blue stain) for the assessment of OARSI score cartilage damage, immunohistochemical staining for the semi-quantitative evaluation of the cellular expression and RTQ-PCR for the quantification of gene expression of the different molecules were carried out. Statistical analysis was performed using Spearman rank correlation or U-Mann Whitney tests. Results: We found a statistically significant linear correlation between OARSI cartilage score and BMI (r=0.64, p=0.0002). The immunohistochemical findings showed a statistically significant linear correlation between cellular expression of leptin and OARSI score (r=0.79, p=0.0001) or BMI (r=0.48, p=0.0001). Likewise, NGF expression correlated with OARSI score (r=0.82, p<0.0001) or BMI (r=0.76, p<0.0001), ADAMTS-5 with OARSI score (r=0.8734, p≤0.0001) or BMI (r=0.55, p=0.001) and MMP-13 with OARSI score (r=0.80, p=0.0001) or BMI (r=0.69, p=0.0001), respectively. No difference in the cellular expression of IL- 17 between OA groups was detected. Concerning IL- 10, we found an inverse linear trend between cellular expression and OARSI score (r=-0.37, p=0.1) and statistically significant inverse linear correlation with BMI (r=-0.823, p<0.000). These findings were confirmed by RTQ-PCR analysis. Conclusions: This study provides further evidence that obesity has not only a mechanical impact on articular cartilage but has also a pro-inflammatory pattern fostering the dysregulation of the activity of chondrocytes and enabling the development of OA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4194